2014
DOI: 10.1021/bm501045k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Proteoglycan-Mimetic Graft Copolymers with Tunable Glycosaminoglycan Density

Abstract: Proteoglycans (PGs) are important glycosylated proteins found on the cell surface and in the extracellular matrix. They are made up of a core protein with glycosaminoglycan (GAG) side chains. Variations in composition and number of GAG side chains lead to a vast array of PG sizes and functions. Here we present a method for the synthesis of proteoglycan-mimetic graft copolymers (or neoproteoglycans) with tunable GAG side-chain composition. This is done using three different GAGs: hyaluronan, chondroitin sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 59 publications
2
46
0
Order By: Relevance
“…[206,208] A peptidoglycan lubricin-mimetic, mLUB15 has also been prepared by similar methodology to that of mAGC using HA binding peptide (GAHWQFNALTVRGGGC) and a type II collagen binding peptide (WYRGRL) attached to the CS backbone [209] (Figure 11b). [210] A further GAG copolymer mimetic aggrecan has been developed using HA as a support backbone to which CS or heparin chains were attached using a hydrazide bi-functional reagent [211] (Figure 10i). Summary of the different forms of GAG polymers which have been assembled for tissue engineering applications.…”
Section: Production Of Biomimetic Neo-aggrecanmentioning
confidence: 99%
“…[206,208] A peptidoglycan lubricin-mimetic, mLUB15 has also been prepared by similar methodology to that of mAGC using HA binding peptide (GAHWQFNALTVRGGGC) and a type II collagen binding peptide (WYRGRL) attached to the CS backbone [209] (Figure 11b). [210] A further GAG copolymer mimetic aggrecan has been developed using HA as a support backbone to which CS or heparin chains were attached using a hydrazide bi-functional reagent [211] (Figure 10i). Summary of the different forms of GAG polymers which have been assembled for tissue engineering applications.…”
Section: Production Of Biomimetic Neo-aggrecanmentioning
confidence: 99%
“…We (Phillips et al, 2018;Prudnikova et al, 2017;Prudnikova et al, 2018;Sarkar, 2011;Sarkar et al, 2017;Sarkar, Lightfoot-Vidal, Schauer, Vresilovic, & Marcolongo, 2012) and others (Bernhard & Panitch, 2012;Place, Kelly, & Kipper, 2014;Sharma, Panitch, & Neu, 2013;Sharma, Vazquez-Portalatin, Calve, & Panitch, 2016) have been investigating mimics to proteoglycans. We designed, synthesized and characterized biomimetic proteoglycans (BPGs) that mimic the molecular architecture and physical properties of natural proteoglycans.…”
Section: Hartmannmentioning
confidence: 99%
“…[ 34,[45][46][47][48][49][50][51][52][53][54][55] We have demonstrated that PCNs and graft copolymers may mimic the size, composition, and growth factor stabilization and delivery properties of proteoglycans found in native ECM. [ 31,56 ] Other groups have also demonstrated growth factor delivery using GAG-based PCNs. [ 57,58 ] While PCNs may mimic the stabilizing and delivery properties of proteoglycans, they must be incorporated into a tissue scaffold for tissue engineering applications.…”
Section: Nanostructured Gag-based Tissue Scaffolds For Growth Factor mentioning
confidence: 99%